2021
DOI: 10.1186/s12893-021-01171-w
|View full text |Cite
|
Sign up to set email alerts
|

New risk factors of postoperative complications in elective gastrointestinal surgery of elderly patients: a prospective cohort study

Abstract: Background Gastrointestinal surgery in elderly individuals presents unexpected postoperative complications. However, predicting postoperative complications in elderly patients undergoing gastrointestinal surgeries is challenging because of the lack of a reliable preoperative evaluation system. We aimed to prospectively evaluate three new preoperative assessment methods to predict the postoperative complications in elderly patients undergoing elective gastrointestinal surgery. Moreover, we aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In this cohort, the proportion of patients of male sex, with a low serum albumin concentration, and with a prolonged operative time, which are traditionally considered predictors of postoperative complications, was significantly higher in the group with complications of CDc grade ≥II (22,23). Various risk factors and predictors of postoperative complications in gastrointestinal surgical diseases have been reported (24,25).…”
Section: Discussionmentioning
confidence: 76%
“…In this cohort, the proportion of patients of male sex, with a low serum albumin concentration, and with a prolonged operative time, which are traditionally considered predictors of postoperative complications, was significantly higher in the group with complications of CDc grade ≥II (22,23). Various risk factors and predictors of postoperative complications in gastrointestinal surgical diseases have been reported (24,25).…”
Section: Discussionmentioning
confidence: 76%
“…Generally, risk factors for postoperative complications of colorectal surgery include high ASA score, male sex, poor nutritional status, emergency operations, renal failure, diabetes, anemia, and chronic obstructive pulmonary disease [ 24 ]. We previously reported atherosclerosis, male sex, and low skeletal muscle mass as risk factors for postoperative complications in older patients who underwent any type of elective gastrointestinal surgery [ 25 ]. The result of the present study showed that atherosclerosis was a risk factor for postoperative complications in older patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found the incidence of complications after gastrointestinal surgery in the elderly age group to be 14.8%. [ 10 ] Considering this incidence rate, the area under the receiver operating characteristic (ROC) curve (AUC) of 0.7, an alpha error of 0.05, a beta error of 0.1, and a null hypothesis value of 0.5, the calculated sample size was 46 patients in each of the two groups, with and without postoperative complications. Including a 10% possible dropout or missing value, the final sample size was calculated to be 100.…”
Section: Methodsmentioning
confidence: 99%